2016
DOI: 10.35799/jm.5.2.2016.13512
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Dan Pemanfaatan Tumbuhan Obat Suku Dani Di Kabupaten Jayawijaya Papua

Abstract: Penelitian ini bertujuan untuk mengidentifikas spesies tumbuhan yang berkhasiat sebagai obat dan cara penggunaannya sebagai obat tradisional. Metode penelitian yang digunakan adalah survey eksploratif dan Participatory Rural Appraisal melalui wawancara dengan dukun kampung bersamaan dengan pengambilan sampel dan identifikasi tumbuhan obat di lokasi penelitian. Hasil penelitian identifikasi dan pemanfaatan tumbuhan obat di 9 desa di Kecamatan Asologaima, Kurulu dan Wamena, ditemukan 16 spesies tumbuhan obat dar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In realizing the 8th Sustainable Development Goal, decent work and economic growth can be realized through efforts to increase economic productivity by maximizing Indonesia's natural resources, including the wealth of medicinal plants. Indonesia produces medicinal plants or herbs with fertile soil conditions, a good climate, and flora diversity (Mabel, Simbala, & Koneri, 2016). Researchers found that Indonesia's tropical forests have at least 19,871 medicinal plants as traditional ingredients (Indonesia 's Center for Research and Development of Medicinal Plants and Traditional Medicines, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In realizing the 8th Sustainable Development Goal, decent work and economic growth can be realized through efforts to increase economic productivity by maximizing Indonesia's natural resources, including the wealth of medicinal plants. Indonesia produces medicinal plants or herbs with fertile soil conditions, a good climate, and flora diversity (Mabel, Simbala, & Koneri, 2016). Researchers found that Indonesia's tropical forests have at least 19,871 medicinal plants as traditional ingredients (Indonesia 's Center for Research and Development of Medicinal Plants and Traditional Medicines, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Dani Tribe in Jayawijaya, Papua used Imperata cylindrica (L.) P.Beauv. as medicine for influenza and tinea versicolor (Mabel et al 2016); while the leaves of Ceiba pentandra (L.) Gaertn. is used as heartburn medicine by the local people of Maros, South Sulawesi (Hasmawati et al 2020); or Blumea balsamifera (L.) DC.…”
Section: Introductionmentioning
confidence: 99%
“…Dewasa ini, pengobatan dengan menggunakan bahan-bahan yang berasal dari alam masih menjadi trend pilihansebagai terapi komplementer dalam penyembuhan suatu penyakit maupun untuk sebagai rehabilitasi kesehatan. Di Indonesia, penggunaan tanaman obat dalam upaya peningkatan kesehatan telahdilakukansejak berabad-abad yang lalu oleh nenek moyangdan masih dipergunakan sampai saat ini.Pengetahuan ini yang kemudian diwariskan secara turun temurun dan dimanfaatkan dan dikembangkanhingga kini menjadi obat tradisional (Marjori, et.al., 2021 (Simbala, 2016).…”
unclassified